Evaluation of rubber seed oil in feed of giant gourami Osphronemus gouramy L: Growth performance and oxidative stress. Issue 2 (3rd April 2022) - Purnamasari, Tina; Suprayudi, Muhammad Agus; Setiawati, Mia; Fauzi, Ichsan Ahmad; Wasjan,
ABSTRACT: A feeding trial was conducted for 56 days using 50% palm oil + 50% fish oil, 50% palm oil + 50% corn oil, 50% palm oil + 50% heated rubber seed oil, 100% heated rubber seed oil, and 100% nontreated rubber seed oil. Gourami (weight ±17 g/fish) were reared using 122 L aquaria at a density of 15 fish per aquaria. Feeding was conducted until apparent satiation three times daily. The results of the parameters of growth performance, protein retention, and lipids observed in the PhRSO (50% palm oil + 50% heated rubber seed oil) treatment showed a better value compared to the others. Moreover, nRSO (100% nontreated rubber seed oil) treatment demonstrated a higher SOD and lower MDA value, which indicated the presence of oxidative stress. Thus, it can be concluded that either heated rubber seed oil or combination of heated rubber seed oil with palm oil can be utilized as a lipid source for gourami fish.